“La Tribu”: a case of multiple adaptations within the narrative of a fictional Spanish movie - Paes, Anna Catharina de Mendonça (TradTerm, 2023)
The Spanish movie La Tribu allows us to explore possibilities of meaning in different means of communication within the narrative. It starts with a viral video exposing Fidel to public humiliation, making him lose his job and his wife. Alongside Fidel’s ruin and depression, a reggaeton singer records a hit song inspired by Fidel and the hit becomes a videoclip with its own choreography. The objective is to describe four processes of intersemiotic translation or adaptation: from video to news, video to song, from song to choreography in a videoclip, from videoclip to flash mob. Based on concepts such as intersemiotic translation (Jakobson 2003 [1969]), refractions (Lefevere 2012 [2000]) and Linda Hutcheon’s “A Theory of Adaptation” (2013 [2006]), it becomes possible to see each form of adaptation in the movie from different perspectives. The method is a case study, which considers context and specificities of the movie.